2021
DOI: 10.3390/metabo11040251
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metabolomics in Pediatric Asthma: Prediction, Diagnosis and Personalized Treatment

Abstract: Asthma in children remains a significant public health challenge affecting 5–20% of children in Europe and is associated with increased morbidity and societal healthcare costs. The high variation in asthma incidence among countries may be attributed to differences in genetic susceptibility and environmental factors. This respiratory disorder is described as a heterogeneous syndrome of multiple clinical manifestations (phenotypes) with varying degrees of severity and airway hyper-responsiveness, which is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 188 publications
(462 reference statements)
1
33
0
Order By: Relevance
“…Recently, -omics sciences are also applied in OSA patients. The first proteomic approach in OSA dates back to 2018 with the study by Zhang [55], which highlighted how intermittent hypoxemia is associated with the increase in 4 proteins (CRP, haptoglobin, fibronectin, platelet factor 4) released into the extracellular fluid from part of microvesicles of cells subjected to hypoxic insult. Since then, proteomics and metabolomics studies in OSA have intensified, highlighting several molecules that may represent biomarkers of OSA.…”
Section: Sleep-related Breathing Disorders and Omics In Severe Asthmamentioning
confidence: 99%
“…Recently, -omics sciences are also applied in OSA patients. The first proteomic approach in OSA dates back to 2018 with the study by Zhang [55], which highlighted how intermittent hypoxemia is associated with the increase in 4 proteins (CRP, haptoglobin, fibronectin, platelet factor 4) released into the extracellular fluid from part of microvesicles of cells subjected to hypoxic insult. Since then, proteomics and metabolomics studies in OSA have intensified, highlighting several molecules that may represent biomarkers of OSA.…”
Section: Sleep-related Breathing Disorders and Omics In Severe Asthmamentioning
confidence: 99%
“…The reproducibility of metabolomics signatures in asthma may also be checked by comparing results between children and adult studies, since finding similar results will strengthen the possible relevance of detected changes. In fact, several studies in children and in adults have coincided in the main metabolites, at least regarding discrimination between asthma and a healthy state [ 32 , 64 , 88 , 92 , 94 ]. However, comparative studies regarding the capacity to discriminate between asthma inflammatory and/or clinical phenotypes are necessary, although the previously mentioned study by Abdel-Aziz [ 113 ], which showed the capacity of eNose metabolomics in exhaled breath to predict an atopic asthma phenotype in adults and children, is a good example of reproducibility.…”
Section: Reproducibility and Stability Of Asthma-related Metabolic Signatures: Of Validation Cohorts Time Stability Age Sex And Other Facmentioning
confidence: 99%
“…Metabolomics, applied to asthma in children in several studies, has been shown to be able to predict future wheezing and exacerbations, as well as to identify different metabolites in different age groups with the same clinical profile. Thus, with the help of metabolomics, it is possible to predict an outcome for asthmatic children and eventually prevent an unfavourable exacerbation scenario [ 64 , 136 , 137 ]. However, there are comparatively fewer studies in adult asthma that have addressed this issue, in a longitudinal, cohort study.…”
Section: Prognostic Value Of Asthma-related Metabolic Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma in children remains a significant public health challenge affecting 5-20% of children in Europe, associated with increased morbidity and societal healthcare costs. Identifying early diagnostic biomarkers and improving the monitoring of airway dysfunction and inflammatory through non-invasive methods are key goals in successful pediatric asthma management [7].…”
Section: Asthmamentioning
confidence: 99%